Geostare system performance assessment methodology - Hobbs, Stephen E.; Convenevole, Carlo; Monti-Guarnieri, Andrea V.; Wadge, Geoff (IEEE, 2016)
Geosynchronous synthetic aperture radar (GEO SAR) is attracting growing interest due to its potential for flexible and frequent imaging over continental areas. Studies are underway to evaluate mission design options and to investigate enabling technologies. This article outlines a method for assessing mission performance which accounts for actual land-cover distributions and weather statistics to derive statistical estimates of mission performance relative to user-defined requirements. A technical challenge is to account accurately for the effects of surface “clutter”: several methods for this are available and will be evaluated. The methodology is outlined. The performance estimates will be used to refine and validate mission design options and to build evidence for the expected benefits of GEO SAR
Keywords: Clutter; Meteorology; Atmospheric modeling; Radar imaging; System performance; Synthetic aperture radar